Multidimensional factors that influence the intention to practice segregation-at-source of solid waste: an empirical study - Kai, Wah Cheng; Osman, Syuhaily; Md Jusoh, Zuroni; Lau, Jasmine Leby (Growing Science, 2021)
Solid waste generation in Malaysia is one of the challenging environmental issues which are often neglected by local households. The main purpose of this research is to ascertain the mediating effect of environmental concerns (i.e., egoistic, altruistic, and biospheric concerns) between households’ descriptive norm and injunctive norm to practice the segregation-at-source of solid waste. A total of 400 residents living in townships in nine districts in the state of Selangor were selected via a multi-stage sampling method. A self-administrated bilingual questionnaire was used to collect the research data. As for the mediation test, the present research found that egoistic concern and altruistic con-cern mediated the significant relationship between injunctive norm and intention to practice the seg-regation-at-source of solid waste among the households in Selangor. The present research con-cludes with research implications and provides several avenues for future research in order to create a comprehensive understanding of the segregation-at-source of solid waste policy among Malaysian citizens.